Gestão do processo de projeto hidrossanitário - Camila Fonseca Melo Lima (2016)
This study presents a diagnosis on the design process of hydro-sanitary systems in real estate projects, with emphasis on the analysis of the contracts and coordination mechanisms of the projects, including the challenges of implementing the NBR 15575 standard and the BIM (Building Information Modeling). We used the case study method, and conducted semi-structured interviews of different agents: designers, builders, design engineers, and architects. Additionally, other sources of evidence were analyzed, such as drawings, design documents, contracts, and coordination records. The results suggest that deficiencies in the design process of hydro-sanitary systems are primarily due to the late involvement of designers in project design and their discontinued and occasional participation, failing to include the development of the as built and post-occupancy evaluations. Difficulties relative to the implementation of the NBR 15575 standard and BIM can be easily foreseen, as they are unknown and are also very new in the present scenario of projects relative to hydro-sanitary systems. Concerning the management challenges encountered in this work, as well as the gaps previously highlighted in the theoretical framework and confirmed a posteriori by the investigated cases, we propose recommendations resulting in improving the management of the design process for hydro-sanitary systems. By showing the procedural deficiencies and presenting these recommendations, this study adds significant contributions besides the simple diagnosis; it further becomes a source of propositions that impact the performance of buildings and that can be extended to the best market and management practices